Reflections on Brazilian contemporary literature (Revista Crioula, 2022)
Those who study contemporary Brazilian literature are faced with the plurality of authors, styles and themes. In the midst of the quantity, however, some regularities can be found; in the following work we choose to forward some reflections on contemporary Brazilian poetry at two levels of literary analysis: first, we propose a systematization of the prosodic-phonological, semantic and narrative forms, the general and abstract semiotic forms of contemporary Brazilian poetry; then, some of its most recurrent themes are listed and briefly analyzed.